Selected problems of the Catholic Church in People’s Republic of Poland in the implementation of its mission - Krajczyński, Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The author of this paper focuses his interest on the State-Church relations during the period of the People’s Republic of Poland. Considering the threefold tasks of the Church in the world i.e. the ministry of governance, teaching and sanctifying, the author has made an attempt to specify the fundamental problems of a political, social, legal and administrative character encountered by the Catholic Church in the process of implementation of the above mentioned mission in Poland in the years 1945–1989.